Results after introduction of a hip fracture care pathway: comparison with usual care - Svenøy, Stian; Watne , Leiv Otto; Hestnes, Ingvild; Westberg, Marianne; Madsen , Jan Erik; Frihagen , Frede (Acta Orthopaedica, 2020)
Background and purpose — We established a care pathway for hip fracture patients, a “Hip Fracture Unit” (HFU), aiming to provide better in-hospital care and thus improve outcome. We compared the results after introduction of the HFU with a historical control group. Patients and methods — The HFU consisted of a series of measures within the orthopedic ward, such as reducing preoperative waiting time, increased use of nerve blocks, early mobilization, and osteoporosis treatment. 276 patients admitted from May 2014 to May 2015 constituted the HFU group and 167 patients admitted from September 2009 to January 2012 constituted the historical control group. Patients were followed prospectively up to 12 months post fracture. Results — Mean preoperative waiting time was 24 hours in the HFU group and 29 hours in the control group (p = 0.003). 123 patients (47%) in the HFU were started on anti-osteoporosis treatment while in hospital. “Short Physical Performance Battery” score (SPPB) was mean 5.5 in the HFU group and 3.8 in the control group at 4 months (p < 0.001), and 5.7 vs. 3.6 at 12 months (p < 0.001). The mortality rate at 4 months was 15% in both groups. No statistically significant differences were found in readmissions, complications, new nursing home admissions, in Barthel ADL index or a mental capacity test at the follow-ups. Interpretation — We found improved preoperative waiting time and better SPPB score at 4 and 12 months postoperatively after introducing the HFU.